Detection of The Presence of Aflatoxin, Cyclopiazonic Acid and Other Alkaloids in Raisin Juice in Mosul City and its Suburbs - Krmo, May Akram; Al_Rejaboo, Maha Akram Mohammad Ali (South Eastern European Journal of Public Health, 2024)
28 samples of fresh raisin juice were collected randomly from the city of Mosul, the right and left sides, and its suburbs. The samples were collected from the areas of Bashiqa, Hamdaniya, Bartella, Aqra, and Dohuk. The presence of Aflatoxine by the ELISA method and Cyclopiazonic acid (CPA) and other alkaloids by the modified Ehrlich reagent method, where there was a variation in the extent of contamination of the samples with Aflatoxine, ranging from 0.0235 ng/L, the highest concentration in the R1 sample, the sample was from the Bashiqa region, and the source of the raisins was from Mosul herbalists, to the lowest concentration 0.002 ng/L in the two R31 samples. This sample was collected from Mosul, left side, Al-Majmoua Al-Thaqafiya neighborhood, the sample R37 is also from Mosul, left side, Al-Masarif neighborhood. As for the other samples, the concentrations ranged from (0.007, 0.005, 0.013, 0.0135, 0.009, 0.0075, 0.01, and 0.0205, 0.012, 0.003, 0.005, 0.008, 0.017, and 0.002) ng/L. As for Cyclopiazonic acid (CPA), there were samples contaminated with this poison, and there were samples with a small percentage of contamination, as the highest concentration was in samples R2, R3, R5, R7, R8, R9, R12, R13, R15, R19, R20, R34, R35, R37, and R38. The lowest concentration is in samples R1, R6, R17, R22, R23, R39, and R40. There are samples that contain other alkaloids, as in samples R16, R21, R24, and R30. All of these samples were the source of raisins. It is either from Attarin, Mosul or northern Iraq.